2006
DOI: 10.1093/toxsci/kfl088
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Androstane Receptor (CAR) as a Potential Sensing Biomarker of Persistent Organic Pollutants (POPs) in Aquatic Mammal: Molecular Characterization, Expression Level, and Ligand Profiling in Baikal Seal (Pusa sibirica)

Abstract: To characterize the function of constitutive active/androstane receptor (CAR) in aquatic mammals, CAR complementary DNA (cDNA) was cloned from the liver of Baikal seal (Pusa sibirica) from Lake Baikal, Russia, and the messenger RNA (mRNA) expression levels in various tissues/organs of the wild population and the CAR ligand profiles were investigated. The seal CAR cDNA had an open reading frame of 1047 bp encoding 348 amino acids that revealed 74-84% amino acid identities with CARs from rodents and human. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 68 publications
2
34
1
Order By: Relevance
“…49 Our previous study found that CAR mRNA expression was abundant in the liver of the Baikal seal. 25 In addition, our in vitro assay demonstrated that Baikal seal CAR was activated by treatment with PCBs. 25,26 These results imply that exposure to OH-PCBs may alter 5′-deiodinase activities via CAR and/or via production of ROS, leading to low serum T 3 /rT 3 ratios in this species.…”
Section: ■ Results and Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…49 Our previous study found that CAR mRNA expression was abundant in the liver of the Baikal seal. 25 In addition, our in vitro assay demonstrated that Baikal seal CAR was activated by treatment with PCBs. 25,26 These results imply that exposure to OH-PCBs may alter 5′-deiodinase activities via CAR and/or via production of ROS, leading to low serum T 3 /rT 3 ratios in this species.…”
Section: ■ Results and Discussionmentioning
confidence: 78%
“…25 In addition, our in vitro assay demonstrated that Baikal seal CAR was activated by treatment with PCBs. 25,26 These results imply that exposure to OH-PCBs may alter 5′-deiodinase activities via CAR and/or via production of ROS, leading to low serum T 3 /rT 3 ratios in this species. In addition, it is possible that T 3 -regulated gene expression in the Baikal seals might be repressed by increased rT 3 levels, as observed in mice.…”
Section: ■ Results and Discussionmentioning
confidence: 78%
“…The authors point out that levels in nursing females were much lower than those in male adults, due to lactation transfer of DDT from mother to newborns. Sakai et al ( 2006 ) reported on an assay for androstane receptor activity in Russian seals. The authors concluded that DDT was active in their assay and that the lowest observable effect level was comparable to a 10 ppm tissue level.…”
Section: Ddt In Marine Mammalsmentioning
confidence: 99%
“…PCB153 has been shown to also be an agonist for the PXR paralogue CAR (Sakai et al, 2006), although again this was only evident at relatively high concentrations, with significant activations occurring above 20ppm. Whilst our current data may initially appear contradictory to the suggestion that non-coplanar PCBs act as inhibitors of human PXRmediated transcriptional events.…”
mentioning
confidence: 99%